Prognostic and reclassification value of serum cathepsin S over the GRACE risk score in patients with non-ST-segment elevation acute coronary syndrome. (25th November 2020) - Sopova, K; Georgiopoulos, G; Mueller-Hennessen, M; Sachse, M; Vlachogiannis, N; Biener, M; Vafaie, M; Katus, H; Spyridopoulos, I; Giannitsis, I; Stamatelopoulos, K; Stellos, K
Abstract: Background: Cathepsin S is an extracellular matrix degradation enzyme that plays an important role in atherosclerotic cardiovascular disease by inducing vasa vasorum development and atherosclerotic plaque rupture. Purpose: To determine the prognostic and reclassification value of baseline serum cathepsin S after adjustment for the Global Registry of Acute Coronary Events (GRACE) score, which is a clinical guideline recommended risk score in non-ST-segment elevation acute coronary syndrome (NSTE-ACS). Methods: Serum cathepsin S was measured by ELISA in 1, 129 consecutive patients presenting with acute symptoms to the emergency department for whom a final adjudicated diagnosis of NSTE-ACS was made. All-cause mortality or all-cause death/non-fatal myocardial infarction (MI) after a median follow-up of 21 months were evaluated as the primary or secondary study endpoint, respectively. The Net Reclassification Index (NRI) estimated the reclassification predictive value for risk of each end-point of cathepsin S over the GRACE score. Results: After a median follow-up of 21 months 101 (8.95%) deaths were reported. The combined endpoint of death or non-fatal MI occurred in 176 (15.6%) patients. Dose-response curve analysis adjusted for the effect of age, gender, diabetes mellitus, high-sensitivity-cardiac troponin T, high-sensitivity C-reactive protein, revascularization and index diagnosis revealed a non-linear association of continuous cathepsin S with all-cause death (P=0.036 for non-linearity; adjusted HR=1.60 for 80th vs. 20th percentiles, P=0.038) or with the combined endpoint (P=0.008 for non-linearity, adjusted HR=1.53 for 80th vs. 20th percentiles, P=0.011). Serum cathepsin S maintained its predictive value for all-cause death (adjusted HR=1.70 highest vs. lowest tertile, 95% CI 1.03–2.82, P=0.039) after adjusting for the GRACE Score. Similarly, cathepsin S predicted the combined endpoint of all-cause death or non-fatal MI (adjusted HR=1.67 highest vs. lowest tertile, 95% CI 1.15–2.42, P=0.007) independently of the GRACE Score. When cathepsin S was added over the GRACE Score it correctly reclassified risk for all-cause death in 20% of the population (P=0.004). Similarly, serum Cathepsin S conferred a significant reclassification value over the GRACE score for all-cause death or non-fatal MI in 15.9% of the population. Conclusions: Serum cathepsin S is a predictor of mortality and improves risk stratification over the GRACE score in patients with NSTE-ACS. The clinical application of cathepsin S as a novel biomarker in NSTE-ACS should be further explored and validated. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): German Heart Foundation